2011
DOI: 10.1111/j.1757-1707.2011.01104.x
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity and the mitigation of climate change through bioenergy: impacts of increased maize cultivation on farmland wildlife

Abstract: The public promotion of renewable energies is expected to increase the number of biogas plants and stimulate energy crops cultivation (e.g. maize) in Germany. In order to assess the indirect effects of the resulting land-use changes on biodiversity, we developed six land-use scenarios and simulated the responses of six farmland wildlife species with the spatially explicit agent-based model system ALMaSS. The scenarios differed in composition and spatial configuration of arable crops. We implemented scenarios w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 41 publications
2
48
3
Order By: Relevance
“…plant protection and fertilisation). Therefore, such systems do not improve the conditions for farmland biodiversity but could rather aggravate the situation with covering a high proportion of the UAA [17]. Oilseed rape, as a mass flowering crop, can provide food resources for pollinating insects but only during a limited period of the year [69].…”
Section: A1: First-generation Energy Crop Production On Productive Agmentioning
confidence: 99%
See 1 more Smart Citation
“…plant protection and fertilisation). Therefore, such systems do not improve the conditions for farmland biodiversity but could rather aggravate the situation with covering a high proportion of the UAA [17]. Oilseed rape, as a mass flowering crop, can provide food resources for pollinating insects but only during a limited period of the year [69].…”
Section: A1: First-generation Energy Crop Production On Productive Agmentioning
confidence: 99%
“…[14,15]). A number of spatially explicit modelling studies have also emerged to evaluate the biodiversity responses from energy crop production at regional, national and pan-national scales, maize in particular [16][17][18][19], some of which considered land-use change scenarios involving energy crop cultivation on marginal land of high nature value [20,21]. In addition, many field-scale or empirical studies with a focus on a particular energy crop have been conducted to compare biodiversity impacts with those of row crops or grasslands [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…The underlying cause of the increase in skylark numbers with landscape fragmentation was the temporal variation in food availability. With small fields, there was a higher diversity of vegetation types within the home range of the skylarks, and hence better foraging opportunities for birds while incubating and raising chicks; but this is only the case, when a variety of crops are grown in the fields (Gevers et al, 2011;Topping and Odderskaer, 2004), hence the reversal of the effect of landscape structure with the CROP scenario. Such effects can also be seen in real world studies.…”
Section: Discussionmentioning
confidence: 96%
“…However, while the number of skylarks is the highest until 2035 compared with the other scenarios, a sharp decrease was observed afterwards that can be explained by the large expansion of bioenergy cropping occurring in this scenario. Other simulation studies based on LUCC scenarios have shown the negative impact of bioenergy crops on wildlife at different spatial levels (Eggers et al, 2009;Gevers et al, 2011). In the latter study, an individual based model of skylark was used and the effect of land use scenarios was analysed.…”
Section: Impacts Of Socio-economic Contexts On Farmer Behaviour and Smentioning
confidence: 99%